24 Gāyatrī sādhanā : vibhinna devī devatāoṃ ke liye 24 Gāyatrī mantroṃ ke vivecana, adhyayana, aura nidhāna sahita - Gautama, Camanalāla, 1929- (Saṃskrti Saṃsthāna, 1977)
Interpretative study, with hymns for worship, of the twenty-four forms of Gāyatrī, Hindu deity.